The Relationship between Academic Self-Efficacy and Cognitive Learning Outcomes of High School Students in Biology Subjects through Problem-Based Learning Model - Gamar Shamdas (Postgraduate, University of Mataram, 2023)
Self-efficacy in the classroom is the belief that one can successfully complete any academic task.. Pre-experimental research with a quantitative approach aims to describe the connection between secondary school understudy's academic self-efficacy and cognitive learning outcomes in biology lessons and to describe gender associations with academic self-efficacy. The One-Shot Case Study research design was carried out in a high school in Palu City for Class XI students, a population of 7 classes totaling 200 students. One class sample consists of 32 students, determined completely randomly. Academic self-efficacy data were acquired through questionnaires, and outcomes of cognitive learning from multiple-choice tests. Information investigation of the connection between academic self-efficacy and cognitive learning outcomes used a simple linear regression test. The association of gender with academic self-efficacy used the Point-Bivariate Correlation test. The result of the research is that there is a relationship between academic self-efficacy and cognitive learning outcomes, and students' cognitive learning outcomes can be predicted through the regression equation y = 25.651 + 1.733x, meaning that an increase in academic self-efficacy scores of 1 point will increase students' cognitive learning outcomes scores of 1.733. Gender significantly correlates with academic self-efficacy, r = 0.841, p = 0.001. This means that the closeness of the gender relationship with the academic self-efficacy of high school students is in the very strong category at 1% significance.